The generalized relative pairs IBD distribution: its use in the detection of linkage - Quan Zou (Frontiers Media S.A., 2016)
I introduce a novel approach to derive the distribution of disease affectional status given alleles identical by descent (IBD) sharing through ITO method. My approach tremendously simplifies the calculation of the affectional status distribution compared to the conventional method which requires the parental mating information, and could be applied to disease with both dichotomous trait and quantitative trait locus (QTL). This distribution is shown to be independent of relative relationship and be employed to develop the marker IBD distributions for relative relationship. In addition, Three linkage tests: the proportion, the mean test, and the LOD score test are proposed for different relative pairs based on their marker IBD distributions. Among all three tests, the mean test for sib pair requires the least sample size, thus, has the highest power. Finally, I evaluate the significance of different relative relationships by a Monte Carlo simulation approach.